When to pay Tax Moratorium Interest? - Núñez Rivas, Silvia Ysabel (2014)
The present article discusses when the tax moratorium interest as part of the tax debt is generated, and which judicial way to discuss its payment. For this purpose, the author starts developing the explicit constitutional principles that are limits to the taxing power of the State; and then she makes a compilation of the judgments of the Constitutional Court regarding the application of the tax moratorium interests.